Quality Characteristics and Essential Oil Properties of Thymus capitatus, Mentha piperita, and Sideritis cypria Dried under Different Conditions - Xylia, Panayiota; Chrysargyris, Antonios; Tomou, Ekaterina Michaela; Goumenos, Christos; Skaltsa, Helen; Tzortzakis, Nikos G. (My University, 2024)
The drying of medicinal and aromatic plants (MAPs) is one of the main preservation methods for these products that can prolong their shelf life, if performed properly. The current study aimed to examine the effects of different drying conditions (sun, shade, and oven drying at 42 °C) on the quality characteristics of Thymus capitatus, Mentha piperita, and Sideritis cypria; their essential oil (EO) yield; and their biological properties (antioxidant and antibacterial activities). According to the results of the current study, oven drying resulted in faster moisture loss for all investigated species and slightly darker products. For T. capitatus, sun drying resulted in higher EO carvacrol content, whereas EOs obtained from shade and oven drying (at 42 °C) presented high total phenolic content and great antimicrobial activity. For M. piperita, shade drying resulted in a higher EO yield and higher iso-menthone content, whilst the EO obtained from oven-dried mint plants presented great antibacterial activity against the investigated foodborne pathogens. S. cypria plants dried in an air-ventilated oven produced an EO rich in β-caryophyllene and α-pinene, which also presented great antioxidant and antibacterial activity. The findings of the current study indicate that traditional drying methods, such as sun and shade, can result in good-quality dried MAPs that can yield EOs with significant biological activities, along with minimum energy consumption and lower carbon dioxide production (lower environmental carbon footprint), as opposed to oven drying. However, the drying-process duration could be a limitation at the industrial scale.
Keywords: Cyprus ironwort; biological activities; drying process; energy consumption; thyme; mint